Cancer Cell‐targeted and Activatable Photoimmunotherapy Spares T Cells in a 3D Coculture Model. (13th October 2019) - Kercher, Eric M.; Nath, Shubhankar; Rizvi, Imran; Spring, Bryan Q.
Abstract: Photodynamic therapy (PDT) is an established therapeutic modality that uses nonionizing near‐infrared light to activate photocytotoxicity of endogenous or exogenous photosensitizers (PSs). An ongoing avenue of cancer research involves leveraging PDT to stimulate antitumor immune responses; however, these effects appear to be best elicited in low‐dose regimens that do not provide significant tumor reduction using conventional, nonspecific PSs. The loss of immune enhancement at higher PDT doses may arise in part from indiscriminate damage to local immune cell populations, including tumor‐infiltrating T cells. We previously introduced "tumor‐targeted, activatable photoimmunotherapy" (taPIT) using molecular‐targeted and cell‐activatable antibody–PS conjugates to realize precision tumor photodamage with microscale fidelity. Here, we investigate the immune cell sparing effect provided by taPIT in a 3D model of the tumor immune microenvironment. We report that high‐dose taPIT spares 25% of the local immune cell population, five times more than the conventional PDT regimen, in a 3D coculture model incorporating epithelial ovarian cancer cells and T cells. These findings suggest that the enhanced selectivity of taPIT may be utilized to achieve local tumor reduction with sparing of intratumor effector immune cells that would otherwise be lost if treated with conventional PDT. Abstract : A targeted, activatable photosensitizer immunoconjugate was synthesized and compared to its untargeted analogue. We hypothesized that cancer cells that overexpress epidermal growth factor receptor preferentially take up and activate the immunoconjugate compared to surrounding cell types, whereas the untargeted photosensitizer is indiscriminately distributed. This was tested in a 3‐dimensional coculture model of human ovarian cancer cells and murine T cells. We showed that T cells are spared after photodynamic treatment with the targeted immunoconjugate compared to the conventional therapy.